2012
DOI: 10.1016/j.dam.2011.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Clique separator decomposition of hole-free and diamond-free graphs and algorithmic consequences

Abstract: Clique separator decomposition introduced by Tarjan and Whitesides is one of the most important graph decompositions. A graph is an atom if it has no clique separator. A hole is a chordless cycle with at least five vertices, and an antihole is the complement graph of a hole. A graph is weakly chordal if it is hole-and antihole-free. K 4 − e is also called diamond. Paraglider has five vertices four of which induce a diamond, and the fifth vertex sees exactly the two vertices of degree two in the diamond. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…, 6 we define sets A i , A + i , A − i , and Q, with respect to G, v and H, as in the last paragraph of Section 2. Then we have the following properties: 4 , v 5 , x, z} induces a graph which is isomorphic to H 4 in G, a contradiction to Lemma 1. So, A + 2 = ∅, and the claim holds.…”
Section: (Smentioning
confidence: 89%
See 1 more Smart Citation
“…, 6 we define sets A i , A + i , A − i , and Q, with respect to G, v and H, as in the last paragraph of Section 2. Then we have the following properties: 4 , v 5 , x, z} induces a graph which is isomorphic to H 4 in G, a contradiction to Lemma 1. So, A + 2 = ∅, and the claim holds.…”
Section: (Smentioning
confidence: 89%
“…∈ E, and then since {x, a 1 , b 1 , p, t} does not induce a co-chair in G, xp ∈ E. Then since {x, b 1 , p, a 2 , q} does not induce a co-chair in G, xq ∈ E. But, now 4 , p} induces an S 1,1,3 in G, which is a contradiction. Thus, G is H 6 -free.…”
Section: Introductionmentioning
confidence: 93%
“…Finally, this work furthers the knowledge about diamond-free graphs. In 1984, Tucker proved the Strong Perfect Graph Conjecture, now Strong Perfect Graph Theorem, for diamond-free graphs [42], and more recently there has been an increased interest regarding the coloring problem and the chromatic number of diamond-free graphs and their subclasses (see, e.g., [11,17,29,31]). Diamond-free graphs also played an important role in a recent work of Chudnovsky et al [15] who proved that there are exactly 24 4-critical P 6 -free graphs.…”
Section: Introductionmentioning
confidence: 99%
“…Using the approach of [5,6], Basavaraju, Chandran and Karthick in [1] showed that the MWIS problem can be solved in polynomial time for hole-and dart-free graphs by reducing it first to hole-, dart-, and gem-free graphs (which are hole-and paraglider-free). We extend previous results and show:…”
Section: Introductionmentioning
confidence: 99%
“…In [6], it was shown that the atoms of the graphs in the class (i) are weakly chordal or specific graphs, and in [5], it was shown that the prime atoms of the graphs in the class (ii) are nearly weakly chordal, from which polynomial time algorithms for MWIS on these graphs follow.…”
Section: Introductionmentioning
confidence: 99%